A study on the implementation of energy management system (EnMS) in the green building / Muhd Asyraf Mat Nazir - Mat Nazir, Muhd Asyraf (Faculty Architecture, Planninng and Surveying, 2015)
The maintenance management is the act or skill of controlling and making decisions about a maintenance process. Facilities management and building maintenance are related because understanding of the process of maintenance is "maintenance management" and the understanding of building facilities maintenance is "building maintenance management". Maintenance have two main types, there are planned maintenance and unplanned maintenance. The building maintenance is important as its preserve the heritage by extending their lifespan, preserving resources in order to reduce the need for new materials, maintaining the aesthetic values of a building at its finest, ensuring the safety of inhabitants and minimizing the production loss from failures. The objectives of the maintenance management are as follows: 1. To ensure that the functional requirements of the facility are attained at all times. 2. To create a conducive and tenantable accommodation for owners and occupants users. 3. To enhance the quality of building structure to meet modern day requirements. 4. To prolong the life span of the building. 5. To preserve the physical characteristic of the building and associated services so as to reflect fewer breakdowns and thereby reduce the probability of early failure. 6. To ensure the assets are kept at reasonable standard and at least cost. 7. To maximize the economic and financial returns from the use of the building. 8. To ensure the safety of the user/occupants. Jabatan Kerja Raya (JKR), Kemuncak Facility Management Holding (KFM) and Gemilang Maintenance are the case studies that have been chosen in Malaysia. For international comparison between Malaysia and other country, Hong Kong is chosen as the case study to be compared based on the scope of works, professional bodies, guidelines and current practice. In conclusion, we hope the content of this assignment can be easily to understand and useful to others who needs.